Episodic Behavioural Regression in an 8-Year-Old Female: Sequelae of 22q11.2 Duplication Syndrome. (9th August 2018) - Bahji, A.; Khalid-Khan, S.
Abstract : 22q11.2 duplication syndrome is a recently discovered genetic syndrome with unclear neuropsychiatric sequelae. While its connection to 22q11.2 deletion syndrome is actively investigated, case reports on the neuropsychiatric sequelae of affected individuals have been previously described, largely focusing on comorbid autism spectrum disorder. Here, we present the case of an 8-year-old female experiencing episodes of severe behavioural regression following medical illness. We analyze the case and relate it to the available literature and identify potential risk factors.